2001
DOI: 10.1002/glia.1036
|View full text |Cite
|
Sign up to set email alerts
|

Role of the astrocytic ETB receptor in the regulation of extracellular endothelin‐1 during hypoxia

Abstract: Astrocytes are known to possess an effective endothelin (ET) eliminatory system which involves astrocytic ET(A) and ET(B) receptors and may become particularly relevant under pathophysiological conditions. The present study has therefore been designed to explore the effect of standardized hypoxia on extracellular concentrations of endothelin-1 (ET-1) and on endothelin-converting enzyme (ECE) activity in primary rat astrocytes genetically (sl/sl) or experimentally (dexamethasone) deficient in ET(B) receptors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 34 publications
0
27
0
2
Order By: Relevance
“…Endothelin-1 (ET-1) is implicated in many CNS pathologies that involve reactive gliosis (Jiang et al, 1993;Yamashita et al, 1994;Zhang et al, 1994;Nie and Olsson, 1996;Stiles et al, 1997;Baba, 1998;Hasselblatt et al, 2001Hasselblatt et al, , 2003Egnaczyk et al, 2003;Sofroniew, 2005). Expression of ET-1 and its receptors (ET-Rs) is strongly upregulated in astrocytes after brain injury (Jiang et al, 1993;Zhang et al, 1994;Hino et al, 1996;Nie and Olsson, 1996;Rogers et al, 1997;Sakurai-Yamashita et al, 1997;Baba, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelin-1 (ET-1) is implicated in many CNS pathologies that involve reactive gliosis (Jiang et al, 1993;Yamashita et al, 1994;Zhang et al, 1994;Nie and Olsson, 1996;Stiles et al, 1997;Baba, 1998;Hasselblatt et al, 2001Hasselblatt et al, , 2003Egnaczyk et al, 2003;Sofroniew, 2005). Expression of ET-1 and its receptors (ET-Rs) is strongly upregulated in astrocytes after brain injury (Jiang et al, 1993;Zhang et al, 1994;Hino et al, 1996;Nie and Olsson, 1996;Rogers et al, 1997;Sakurai-Yamashita et al, 1997;Baba, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of ET-1 and its receptors (ET-Rs) is strongly upregulated in astrocytes after brain injury (Jiang et al, 1993;Zhang et al, 1994;Hino et al, 1996;Nie and Olsson, 1996;Rogers et al, 1997;Sakurai-Yamashita et al, 1997;Baba, 1998). Astrocytes are autocrine targets of ET-1 action, which results in increased cell proliferation (Lazarini et al, 1996;Hasselblatt et al, 2001Hasselblatt et al, , 2003Rogers et al, 2003;Desai et al, 2004). A direct role for ET-1 in reactive gliosis was demonstrated by in vivo infusion of exogenous ETs or ET-R agonists, which caused astrocyte hypertrophy and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ET-1 affects numerous cell functions of cultured astrocytes such as control of ion channel activity (5), glutamate efflux (52) and uptake (41), glucose utilization (58), permeability of gap junction communications (3, 16), and calcium signaling (3, 64). In turn, astrocytes are a major source of ET-1 (12, 13) and seem to play an important role in the regulation of ET-1 levels within the CNS (14,24,25).In contrast to the cerebrovascular system, in which ET A receptors are the major receptor subtype, astrocytes predominantly express the ET B receptor subtype (26,38). However, at least in cultured astrocytes, there has also been evidence of ET A receptor mRNA expression (13) and an ET A /ET B hybrid receptor has been postulated (31).…”
mentioning
confidence: 99%
“…Several studies have shown that ET-1 affects numerous cell functions of cultured astrocytes such as control of ion channel activity (5), glutamate efflux (52) and uptake (41), glucose utilization (58), permeability of gap junction communications (3,16), and calcium signaling (3,64). In turn, astrocytes are a major source of ET-1 (12,13) and seem to play an important role in the regulation of ET-1 levels within the CNS (14,24,25).…”
mentioning
confidence: 99%
“…Il a été montré in vitro que la leptine induisait une stimulation de la synthèse et de la sécrétion d'ET-1 à partir de cultures primaires de cellules endothéliales [16]. Une inhibition de la production d'ET-1 par les astrocytes soumis à une hypoxie, associée à une augmentation d'activité ECE-1 à été mise en évidence [17]; cette inhibition n'est pas retrouvée dans les cultures d'astrocytes issus d'animaux invalidés pour le gène ET-B. Dans les cellules endothéliales cultivées en hypoxie, les facteurs AP-1 (activating protein-1), GATA-2 et NF-1 (nuclear factor-1) sont impliqués dans la stabilisation de la liaison du facteur HIF-1 (hypoxia-inducible factor-1) sur le promoteur d'ET-1 en induisant le recrutement de la protéine p300/CBP (CREB binding protein) [18].…”
Section: Modulation Du Système Endothélineunclassified